A new approach to the 8b-azaacenaphthylene ring system1. Issue 38 (14th October 2015) - Kamath, Anushree; Fabritius, Charles-Henry; Philouze, Christian; Delair, Philippe
<x xml:space="preserve">Abstract</x> A new approach to the 8b-azaacenaphthylene ring system is described featuring several stereoselective transformations.